Analysis of the Misuse of Legal English Terminology in Legal Scientific Work Abstracts - Satyayudha Dananjaya, Nyoman; Ayu Asty Senja Pratiwi, Putu; Aras Samsithawrati, Putu (Udayana Journal of Social Sciences and Humanities; Vol 2 No 1 (2018): UJoSSH, Feburary 2018DO - 10.24843/UJoSSH.2018.v02.i01.p01, 2018)
Scientific work in law field has its own characteristics, including the legal English terminology. Legal English is actually slightly different with general English. Nowadays, there are lots of inappropriate process of language transfer from Bahasa to English can be found especially in abstract, as part of the scientific work related to law field. Thus, such issue will affect the abstract validity as a representation of the contents of the scientific work as a whole. This study used an empirical juridical approach which employed non-probability sampling technique and qualitative descriptive analyses. The results show that the misuse of legal English terminology towards abstract of legal, scientific works may occur due to word-for-word translation, free translation, and literal translation. Based on empirical research, such misuse occurred due to the use of online translation engine which mostly caused by the ignorance of abstract’s authors on the structure of standard academic writing (S- P-O)in the source language and asking help from colleagues who mostly do not have legal background and has minimum knowledge of legal English terminology.